Исследование влияния лесных массивов на дальность связи в сетях ZigBee - Галкин, Павел Викторович; Головкина, Людмила Вячеславовна; Борисенко, Анна Сергеевна (Eastern-European Journal of Enterprise Technologies, 2011)
Article is devoted to the influence of forest depending on distance communication in wireless sensor networks, ZigBee. Calculate the damping signal in forest